A Survey on the Differences of Using User Story and Tasks in the ASD Effort Estimation in Brazil - de Morais, Diego; Almeira Jr., Jorge Rady; Siqueira, Fabio Levy (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2022)
This paper investigates the state of the practice of ASD estimation based on User Stories. We conducted a survey with 85 Brazilian professionals experienced in ASD estimating. The survey analyzes what is used in the estimation (User Story, task, or both), its differences, how the estimate is made (especially if there is any segmentation), and the average precision of the effort estimates. The main findings are: 1) Planning Poker is the most used technique and points with a Fibonacci scale as a metric; 2) User Stories are broken down into tasks in the vast majority of teams; 3) Teams that estimate both: User Stories and tasks/subtasks showed greater accuracy compared to the others; 4)At least ¼ of the teams make estimates for the team segmenting by some criteria.